Regulation of Incest Crimes: A Comparative Criminal Law Perspective from Indonesia, Germany, and Yemen - Deryasa; Muhammad Hasan Abdurrahman; Muchammad Fatich (Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Incest, commonly understood as sexual relations between blood relatives, remains a legal dilemma in many countries because it conflicts with moral, religious, and social values, from the family unit to society at large. This study aims to compare criminal law regulations concerning incest offenses in Indonesia, Germany, and Yemen. These three countries were selected based on theoretical considerations and differences in their legal systems: Indonesia, which emphasizes a hybrid legal system that combines civil law with religious and local values; Germany, which represents a Western secular legal system; and Yemen, which adopts a Sharia-based legal system. This study employs a normative legal research approach with a comparative perspective, and the data were collected through a literature review. The findings indicate that the criminalization of incest is not merely determined by the existence or absence of legal prohibitions but is shaped by different legal rationales that are reflected in each country's legislation, including Indonesia’s Criminal Code (KUHP), Germany’s Criminal Code (Strafgesetzbuch/StGB), and Yemen’s qanun regulations. This study contributes by providing a cross-legal-system analytical framework for policymakers in Indonesia in formulating contextual regulations on incest, while also enriching legal scholarship through comparative analyses of criminal law policy.